Assessments of medicinal plant usage for the traditional treatment of skin diseases in Akinyele Local Government Area, Ibadan, Oyo State, Nigeria - Ariyo, Oluyinka Christopher; Usman, Bello Mohammed; Adelani, Olusegun David; Ariyo, Oluyemisi Mary (Ethnobotany Research and Applications, 2021)
Background: Skin diseases is one of the major health concerns worldwide because it affects people of all ages and gender from neonates to the elderly and constitute one of the five reasons for medical consultation. The study was designed to assess medicinal plants used for traditional treatment of skin diseases in Akinyele Local Government Area, Oyo State, Nigeria Methods: A total number of 320 respondents comprising of herbalist, herb sellers, hunters and farmers were selected randomly from eight villages within the study areas. Information on the medicinal plant used for traditional treatment of skin diseases was collected by semi-structured questionnaires administered to the respondents one-on-one in the local language (Yoruba) of the people. The data collected were analysed using descriptive statistics such as tables, percentages, pie charts, bar charts, Frequency of Citation (FC), Relative Frequency of Citation (RFC), Family Importance Value (FIV) and Plant Part Value (PPV) Results: The study revealed that 41 plant species from 25 families were used to treat 10 different types of skin disorders in the study area. The most represented families are Fabaceae and Rubiaceae. RFC ranged from 0.009 to 0.391.The most cited plant species are Jatropha curcas Linn. (RFC = 0.391), Ricinus communis L. (RFC = 0.313) and Entandrophragma cylindricum (Sprague) Sprague (RFC = 0.284). Trees are the most used plant form while bark is the most widely used plant parts (PPV = 0.373). The most common method of preparation was by decoction and the major route of administration of recipes was oral. Conclusion: The study concludes that medicinal plants have great potentials to treat different kind of skin diseases and the respondents have vast knowledge of their usage. However, government should ensure a synergy between the manufacturers of herbal medicine, professional in the field of traditional and alternative therapies with the aim to synthesis them into the healthcare delivery system of Nigerian. Key words: Medicinal plants, Herbal medicine, Traditional treatment, Skin diseases